The ligand occupancy of endothelial protein C receptor switches the protease-activated receptor 1-dependent signaling specificity of thrombin from a permeability-enhancing to a barrier-protective response in endothelial cells - Bae, Jong-Sup; Yang, Likui; Manithody, Chandrashekhara; Rezaie, Alireza R (Blood, 2007)
Recent studies have indicated that activated protein C (APC) may exert its cytoprotective and anti-inflammatory activities through the endothelial protein C receptor (EPCR)-dependent cleavage of protease-activated receptor 1 (PAR-1) on vascular endothelial cells. Noting that (1) the activation of protein C on endothelial cells requires thrombin, (2) relative to APC, thrombin cleaves PAR-1 with approximately 3 to 4 orders of magnitude higher catalytic efficiency, and (3) PAR-1 is a target for the proinflammatory activity of thrombin, it is not understood how APC can elicit a protective signaling response through the cleavage of PAR-1 when thrombin is present. In this study, we demonstrate that EPCR is associated with caveolin-1 in lipid rafts of endothelial cells and that its occupancy by the gamma-carboxyglutamic acid (Gla) domain of protein C/APC leads to its dissociation from caveolin-1 and recruitment of PAR-1 to a protective signaling pathway through coupling of PAR-1 to the pertussis toxin-sensitive G(i)-protein. Thus, when EPCR is bound by protein C, the PAR-1 cleavage-dependent protective signaling responses in endothelial cells can be mediated by either thrombin or APC. These results provide a new paradigm for understanding how PAR-1 and EPCR participate in protective signaling events in endothelial cells.